A ZIF / GO-based synergistic corrosion-inhibiting filler and its preparation method and application
By using ZIF/Go basic coordinated corrosion fillers in the coatings, using the synergies of ZIF and GO to solve the compatibility and release control problems of the corrosion agent in the coatings, and realize the high anticorrosive performance and durability. It is suitable for it to be suitable for Among multiple coatings.
Patent Information
- Application Number
- CN202410432502.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-11
AI Technical Summary
In the prior art, corrosion inhibitors have poor compatibility in coatings and are difficult to control release, resulting in excessive consumption and may accelerate corrosion.
The ZIF/GO foundation coordinated corrosion fillers are used to compose ZIF by loading small molecules on the surface of graphene GO GO surface, and synthetic with phenolic nitrate and phenylzole organic ligand in situ to form a composite filler. Under the corrosion conditions, ZIF will decompose the release of organic ligand corrosion, and the Go surface releases small -purine small molecules.
The high anticorrosive performance and persistence are achieved, the amount is less, and the components of other components are good. It is evenly scattered in the coating, simplified the coating process, and reduced the cost.
Smart Images

Figure CN118546554B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrosion and protective coatings, and specifically relates to a ZIF / GO-based synergistic corrosion-inhibiting filler and a preparation method and application thereof. Background Art
[0002] Metal materials are widely used in all aspects of industry and life. However, metal corrosion is widely distributed in the process of metal use, and the economic losses caused cannot be underestimated. To solve this problem, corrosion inhibitors and coating protection technologies are usually used to control metal corrosion. When the coating is partially damaged, if the system can release the corrosion inhibitor to the exposed metal surface, this will greatly improve the service life and protective performance of the coating. How to make the corrosion inhibitor molecules stably exist in the coating and be able to be intelligently released when the coating is damaged is becoming a core issue in the field of coating corrosion inhibitor composite protection research.
[0003] Although it is simple to add the corrosion inhibitor directly to the coating, it leads to poor compatibility of the coating, making it difficult to control the release of the corrosion inhibitor, resulting in a large amount of consumption and possibly accelerating corrosion. In the prior art, the corrosion inhibitor is generally added to a microcapsule or a nanocontainer, and then doped into the coating. For example, patent CN202211287183.0 discloses a functional filler, a self-repairing anti-corrosion coating and a preparation method, wherein an organic corrosion inhibitor is loaded into polyaniline-modified halloysite nanotubes. The functional filler is applied to a water-based anti-corrosion coating, which can effectively enhance the corrosion inhibition effect of the coating on the damaged part and realize the self-repairing performance of the coating. Patent CN202011616153.0 discloses a MOF-loaded corrosion inhibitor filler, a self-repairing anti-corrosion coating and a preparation method thereof, wherein the filler is a metal organic framework compound hmt-MOF as a capsule shell and an encapsulated corrosion inhibitor as a capsule core, which can react with the functional groups in the resin, has good compatibility, is easy to disperse, has high storage stability, and at the same time enhances the adhesion and anti-corrosion performance of the coating to the substrate. CN202210336957.8 discloses a polypyrrole-wrapped graphene corrosion inhibitor container, a preparation method thereof, a composite coating and an application thereof. A polypyrrole-wrapped graphene corrosion inhibitor container is obtained by mixing a corrosion inhibitor solution, a graphene oxide dispersion and an initiator for polymerization reaction. Polypyrrole can be used to adjust the release rate of the corrosion inhibitor, so that it is released quickly in an alkaline solution and released at a slower rate in a neutral medium. Excellent anti-corrosion performance and anti-corrosion durability can be achieved in the coating.
[0004] The corrosion inhibitor fillers in the above patents have certain defects when applied to coatings. For example, the corrosion inhibitor carrier will have a certain impact on the performance of the coating itself; or the corrosion inhibitor carrier is not efficient in releasing the corrosion inhibitor; or the effect of the loaded corrosion inhibitor needs to be improved; or the surface coating process of the corrosion inhibitor carrier is difficult to achieve. Summary of the invention
[0005] The purpose of the present invention is to provide a ZIF / GO-based synergistic corrosion-inhibiting filler and a preparation method and application thereof. The organic ligands in the ZIF material and the purine small molecules loaded on the surface of GO can be used as corrosion inhibitors at the same time. The two corrosion inhibitors work together to make the coating have high corrosion resistance and durability. When used in the coating, the added content is relatively small, and the compatibility with other components of the coating is good, and the coating is evenly dispersed in the coating.
[0006] The technical solution adopted by the present invention to solve the above problems is: a method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler, comprising the following steps:
[0007] (1) After mixing graphene oxide GO with the solution, ultrasonic treatment is performed, and then a corrosion inhibitor is added and stirred, and then an encapsulant is added and stirred to obtain a preliminary solution;
[0008] (2) pre-dissolving zinc nitrate hexahydrate and benzimidazole organic ligand in a solution of the same volume as that in step (1), mixing them evenly and then adding them to the preliminary solution, stirring and reacting at room temperature, and then post-treating to obtain a ZIF / GO-based synergistic corrosion inhibition filler;
[0009] Wherein, the solution in steps (1) and (2) is a mixed solution of deionized water and N,N-dimethylformamide.
[0010] Preferably, in step (1), the volume ratio of the graphene oxide GO, corrosion inhibitor, and encapsulant substance to the solution is 2 mmol: 1 mmol: 2 mmol: 10 ml.
[0011] Preferably, the corrosion inhibitor is one or more of 2-chloromethylbenzimidazole, adenine, and tea polyphenols.
[0012] Preferably, the encapsulant is one of polyether P123 and polyether F188.
[0013] Preferably, in step (2), the volume ratio of zinc nitrate hexahydrate and benzimidazole to the solution is 2 mmol:7 mmol:10 ml.
[0014] Preferably, the volume ratio of the deionized water to N,N-dimethylformamide is 4:5-4:7.
[0015] Preferably, the method specifically comprises the following steps:
[0016] (1) After mixing graphene oxide GO with the solution, ultrasonic treatment is performed for 0.5-1h, and then a corrosion inhibitor is added and stirred for 0.5-1h at 50-70°C under a nitrogen atmosphere, and then an encapsulant is added and stirred for 1-2h to obtain a preliminary solution;
[0017] (2) Zinc nitrate hexahydrate and benzimidazole organic ligand are pre-dissolved in a solution of the same volume as in step (1), mixed evenly, and then added to the preliminary solution. The mixture is stirred at room temperature for 22 to 25 hours. The resulting product is then centrifuged and washed with a mixed solution of deionized water and N,N-dimethylformamide (DMF). Finally, the product is vacuum dried to obtain a ZIF / GO-based synergistic corrosion-inhibiting filler.
[0018] A ZIF / GO-based synergistic corrosion-inhibiting filler is prepared by adopting the preparation method of the ZIF / GO-based synergistic corrosion-inhibiting filler.
[0019] A use of a ZIF / GO-based synergistic corrosion-inhibiting filler in a coating, the coating comprising the following components in percentage by mass: 1-3% of a ZIF / GO-based synergistic corrosion-inhibiting filler, 36-48% of an epoxy resin, 18-24% of a curing agent, 30-45% of a diluent, and 1-5% of other additives; the ZIF / GO-based synergistic corrosion-inhibiting filler is prepared by the above-mentioned method for preparing the ZIF / GO-based synergistic corrosion-inhibiting filler.
[0020] Preferably, the coating formed by the paint is prepared by the following preparation steps: ZIF / GO-based synergistic corrosion-inhibiting filler and epoxy resin in equal mass ratio are fully mixed, and then a curing agent and other additives are added in proportion, and a diluent is added, and the coating is applied to the substrate after surface pretreatment and cured at high temperature to obtain a coating.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] (1) The present invention uses graphene oxide GO with a large specific surface area to load the corrosion inhibitor to achieve the loading amount of the corrosion inhibitor, and fixes it with an encapsulant. At the same time, metal ions and organic ligands that are synergistic corrosion inhibitors are used to synthesize ZIF in situ, so that ZIF is coated on the surface of GO to obtain a composite filler. The composite filler is loaded with two synergistic corrosion inhibitors. Under corrosion conditions, ZIF will decompose the organic ligand corrosion inhibitor benzimidazole due to pH stimulation response, and the GO surface will release purine small molecules as synergistic corrosion inhibitors at the same time. The two corrosion inhibitors work together to make the coating have high anti-corrosion performance and durability.
[0023] (2) The ZIF / GO-based synergistic corrosion-inhibiting filler of the present invention is used in coatings. Its added content is relatively small, and it has good compatibility with other components of the coating. It is evenly dispersed in the coating. There is no need to further hybridize the epoxy resin or add other additives. There is no restriction on the types of epoxy resin and its curing agent, and it can be applied to a variety of coatings.
[0024] (3) As an anti-corrosion coating, the coating process of the present invention is simple and easy to operate, which reduces processing costs and time costs. It is also suitable for large-area construction and has various construction operation methods, and can be used in a variety of occasions and complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM morphology of ZIF / GO in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to the accompanying drawings. Example 1
[0027] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0028] (1) Synthesis of filler: After mixing 10 mmol of GO with 50 ml of solution, ultrasonic treatment was performed for 0.5 h. At a reaction temperature of 50 °C, a reaction speed of 600 r / min, and a nitrogen atmosphere, 5 mmol of 2-chloromethylbenzimidazole was added and stirred for 0.5 h. Finally, 10 mmol of polyether P123 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and added to the preliminary solution. The mixture was stirred and reacted for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain a filler.
[0029] (2) Coating preparation: 1% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 36% E44 epoxy resin, and 18% polyamide 651 curing agent and 2% other additives (1% BYK-054 defoaming agent and 1% BYK-333 leveling agent) were added. Finally, 43% butyl acetate was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating.
[0030] like Figure 1 As shown in the figure, the morphology of the ZIF / GO-based synergistic corrosion inhibition filler prepared in this example is as follows: Figure 1 It can be seen that ZIF / GO presents a sheet-like structure. This is because during the in-situ synthesis process, the hydroxyl groups on GO interact with the metal ions Zn 2+ Adsorption occurs, causing the synthesized ZIF to grow evenly on the surface of GO. Example 2
[0031] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0032] (1) Synthesis of filler: After mixing 10 mmol of GO with 50 ml of solution, ultrasonic treatment was performed for 0.5 h. At a reaction temperature of 60 °C, a reaction speed of 800 r / min, and a nitrogen atmosphere, 5 mmol of 2-chloromethylbenzimidazole was added and stirred for 0.5 h. Finally, 10 mmol of polyether P123 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and added to the preliminary solution. The mixture was stirred and reacted for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain a filler.
[0033] (2) Coating preparation: 2% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 40% E44 epoxy resin, and 20% polyamide 651 curing agent and 2% other additives (1% BYK-054 defoaming agent, 1% BYK-333 leveling agent) were added. Finally, 36% butyl acetate was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating. Example 3
[0034] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0035] (1) Synthesis of filler: After mixing 10 mmol of GO with 50 ml of solution, ultrasonic treatment was performed for 1 h. At a reaction temperature of 70 °C, a reaction speed of 800 r / min, and a nitrogen atmosphere, 5 mmol of adenine was added and stirred for 0.5 h. Finally, 10 mmol of polyether F188 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and then added to the preliminary solution. The mixture was stirred and reacted for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain the filler.
[0036] (2) Coating preparation: 3% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 40% E44 epoxy resin, and 20% polyamide 651 curing agent and 1% other additives (0.5% BYK-054 defoaming agent and 0.5% BYK-333 leveling agent) were added. Finally, 36% butyl acetate was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating. Example 4
[0037] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0038] (1) Synthesis of filler: After mixing 10 mmol of GO with 50 ml of solution, ultrasonic treatment was performed for 1 h. At a reaction temperature of 50 °C, a reaction speed of 400 r / min, and a nitrogen atmosphere, 5 mmol of adenine was added and stirred for 0.5 h. Finally, 10 mmol of polyether F188 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and added to the preliminary solution. The mixture was stirred for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain a filler.
[0039] (2) Coating preparation: 1% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 42% E44 epoxy resin, and 21% polyamide 651 curing agent and 3% other additives (1.5% BYK-054 defoaming agent and 1.5% BYK-333 leveling agent) were added. Finally, 33% dibutyl phthalate was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating. Example 5
[0040] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0041] (1) Synthesis of filler: After 10 mmol of GO was mixed with 50 ml of solution, ultrasonic treatment was performed for 0.5 h. At a reaction temperature of 60 °C, a reaction speed of 500 r / min, and a nitrogen atmosphere, 5 mmol of tea polyphenols was added and stirred for 0.5 h. Finally, 10 mmol of polyether P123 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and added to the preliminary solution. The mixture was stirred and reacted for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain a filler.
[0042] (2) Coating preparation: 2% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 42% E44 epoxy resin, and 21% polyamide 651 curing agent and 2% other additives (1% BYK-054 defoaming agent and 1% BYK-333 leveling agent) were added. Finally, 33% solvent was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating. Example 6
[0043] A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler and its coating application.
[0044] (1) Synthesis of filler: After 10 mmol of GO was mixed with 50 ml of solution, ultrasonic treatment was performed for 0.75 h. At a reaction temperature of 65 °C, a reaction speed of 700 r / min, and a nitrogen atmosphere, 5 mmol of tea polyphenols was added and stirred for 0.5 h. Finally, 10 mmol of polyether F188 was added and stirred for 1 h to obtain a preliminary solution. 10 mmol of zinc nitrate hexahydrate and 14 mmol of benzimidazole organic ligand were pre-dissolved in 50 ml of solution, mixed evenly, and added to the preliminary solution. The mixture was stirred and reacted for 24 h under the same conditions. The obtained product was then centrifuged for 10 min at a speed of 3000 r / min, washed with deionized water and DMF three times, and vacuum dried at 60 °C to obtain a filler.
[0045] (2) Coating preparation: 1% ZIF / GO-based synergistic corrosion-inhibiting filler was thoroughly mixed with 44% E44 epoxy resin, and 22% polyamide 651 curing agent and 1% other additives (0.5% BYK-054 defoaming agent and 0.5% BYK-333 leveling agent) were added. Finally, 32% solvent was added and mixed evenly. The anti-corrosion coating was applied to the surface of the pretreated low-carbon steel plate using a 150 μm coating rod and cured at 100 °C for 1 h to obtain the anti-corrosion coating.
[0046] Comparative Example 1
[0047] Coating preparation: 3% corrosion-inhibiting filler (2% talc, 1% zinc phosphate) was thoroughly mixed with 36% E44 epoxy resin, and 18% polyamide 651 curing agent and 2% other additives (1% BYK-054 defoaming agent, 1% BYK-333 leveling agent) were added. Finally, 41% butyl acetate was added and mixed evenly. The anti-corrosion coating was applied on the surface of the pretreated low-carbon steel plate using a 150-micron applicator rod and cured at 100°C for 1 h to obtain the anti-corrosion coating.
[0048] The coatings of Examples 1 to 6 and Comparative Example 1 were subjected to the following tests respectively.
[0049] Anti-corrosion test: Wuhan Cost Instrument CS310M was used to test the low-frequency impedance of the coating after immersion in a 3.5wt% NaCl solution at 25°C for 30 days.
[0050] Adhesion test: GB / T 5210-2006 standard was used to measure the adhesion of coating samples.
[0051] Contact angle test: The contact angle of the sample was measured using an optical contact angle meter of the Attention Theta Flex model produced by Swedish Biolin Technology Co., Ltd.
[0052] Coating toughness test: The flexibility of the coating film was tested using the method of GB / T 1731-93.
[0053] UV test: Use GB / T 2423.24-2022 method to test UV resistance.
[0054] The test results of each embodiment are shown in Table 1.
[0055] Table 1
[0056]
[0057] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a ZIF / GO-based synergistic corrosion-inhibiting filler, characterized in that: The following steps are involved: (1) After mixing graphene oxide GO with the solution, ultrasonic treatment is performed, and then a corrosion inhibitor is added and stirred, and then an encapsulant is added and stirred to obtain a preliminary solution; (2) pre-dissolving zinc nitrate hexahydrate and benzimidazole organic ligand in a solution of the same volume as that in step (1), mixing them evenly and then adding them to the preliminary solution, stirring and reacting at room temperature, and then post-treating to obtain a ZIF / GO-based synergistic corrosion inhibition filler; Wherein, the solution in steps (1) and (2) is a mixed solution of deionized water and N,N-dimethylformamide; The encapsulant is one of polyether P123 and polyether F188; The corrosion inhibitor is one or more of 2-chloromethylbenzimidazole, adenine and tea polyphenols.
2. The method for preparing the ZIF / GO-based synergistic corrosion inhibition filler according to claim 1, characterized in that: The volume ratio of the graphene oxide GO, corrosion inhibitor, and encapsulant substance to the solution in step (1) is 2mmol:1mmol:2mmol:10ml.
3. The method for preparing the ZIF / GO-based synergistic corrosion-inhibiting filler according to claim 1, characterized in that: The volume ratio of zinc nitrate hexahydrate and benzimidazole to the solution in step (2) is 2 mmol:7 mmol:10 ml.
4. The method for preparing the ZIF / GO-based synergistic corrosion inhibition filler according to claim 1, characterized in that: The volume ratio of the deionized water to N,N-dimethylformamide is 4:5-4:
7.
5. The method for preparing the ZIF / GO-based synergistic corrosion inhibition filler according to claim 1, characterized in that: The specific steps include: (1) After mixing graphene oxide GO with the solution, ultrasonic treatment is performed for 0.5-1h, and then a corrosion inhibitor is added and stirred for 0.5-1h at 50-70°C under a nitrogen atmosphere, and then an encapsulant is added and stirred for 1-2h to obtain a preliminary solution; (2) Zinc nitrate hexahydrate and benzimidazole organic ligand are pre-dissolved in a solution of the same volume as in step (1), mixed evenly, and then added to the preliminary solution. The mixture is stirred at room temperature for 22 to 25 hours. The resulting product is then centrifuged and washed with a mixed solution of deionized water and N,N-dimethylformamide (DMF). Finally, the product is vacuum dried to obtain a ZIF / GO-based synergistic corrosion-inhibiting filler.
6. A ZIF / GO-based synergistic corrosion inhibition filler, characterized in that: The ZIF / GO-based synergistic corrosion-inhibiting filler is prepared by the preparation method of any one of claims 1 to 5.
7. Application of a ZIF / GO-based synergistic corrosion-inhibiting filler in a coating, characterized in that: The coating comprises the following components in percentage by mass: 1-3% ZIF / GO-based synergistic corrosion-inhibiting filler, 36-48% epoxy resin, 18-24% curing agent, 30-45% diluent, and 1-5% other additives; the ZIF / GO-based synergistic corrosion-inhibiting filler is prepared by the preparation method of the ZIF / GO-based synergistic corrosion-inhibiting filler described in any one of claims 1-5.
8. The use of the ZIF / GO-based synergistic corrosion-inhibiting filler in coatings according to claim 7, characterized in that: The coating formed by the coating is prepared by the following preparation steps: the ZIF / GO-based synergistic corrosion-inhibiting filler and the epoxy resin are fully and evenly mixed, and then a curing agent and other additives are added in proportion, and a diluent is added, and the coating is applied on a substrate after surface pretreatment and cured at high temperature to obtain a coating.
Citation Information
Patent Citations
MOF loaded corrosion inhibitor filler, self-repairing anticorrosive coating and preparation method thereof
CN112521837A
A polypyrrole-coated graphene corrosion inhibitor container and its preparation method, and a composite coating and its application.
CN114561118B
A functional filler, a self-healing anti-corrosion coating and its preparation method
CN115948067B
Polypyrrole coated graphene corrosion inhibitor container, preparation method thereof, composite coating and application thereof
CN114561118A
Cited By
BNF-at bimetal MOF-based wave-absorbing corrosion-resistant composite coating and preparation method thereof
CN120737691A